Analysis of Composite Mechanical Strength from Waste Chicken Feather and Sawdust - Aswan Munang; Achmad Zaki Yamani (University of Muhammadiyah Malang, 2021)
The objective of the study is to determine the mechanical strength of chicken feather and sawdust waste in making biocomposites. The use of natural fibers because they are cheap and environmentally friendly. Preparation of biocomocytes with several folume fractions. The volume fraction to be researched is 80%, 20%, 0%, 80%, 15%, 5%, 80%, 10%, 10%, 80%, 5%, 15%, 80%, 0%, and 20%. Biocomposite testing with ASTM E8 specimen standards for tensile testing with a universal testing machine. Impact testing with ASTM E23 specimen standards with an impact testing machine. From the test results, it can be seen that the volume fraction of 80%, 15%, 5%, has the highest tensile strength with 6,390 MPa. Tensile test at a volume fraction of 80%, 15%, 5%, with an impact strength of 0.731 joules. From the research results, it can be concluded that the same volume fraction as the tensile and impact test has a high mechanical strength. The use of the dominant fiber does not affect its mechanical strength. The combination of natural fibers and polymers used will affect its mechanical strength.